Bone Marrow Characteristics Associated With Changes in Infarct Size After STEMI: A Biorepository Evaluation From the CCTRN TIME Trial. Issue 1 (2nd January 2015) - Schutt, Robert C.; Trachtenberg, Barry H.; Cooke, John P.; Traverse, Jay H.; Henry, Timothy D.; Pepine, Carl J.; Willerson, James T.; Perin, Emerson C.; Ellis, Stephen G.; Zhao, David X.M.; Bhatnagar, Aruni; Johnstone, Brian H.; et al.
Abstract : Rationale: : Despite significant interest in bone marrow mononuclear cell (BMC) therapy for ischemic heart disease, current techniques have resulted in only modest benefits. However, selected patients have shown improvements after autologous BMC therapy, but the contributing factors are unclear. Objective: : The purpose of this study was to identify BMC characteristics associated with a reduction in infarct size after ST-segment-elevation–myocardial infarction. Methods and Results: : This prospective study comprised patients consecutively enrolled in the CCTRN TIME (Cardiovascular Cell Therapy Research Network Timing in Myocardial Infarction Evaluation) trial who agreed to have their BMCs stored and analyzed at the CCTRN Biorepository. Change in infarct size between baseline (3 days after percutaneous coronary intervention) and 6-month follow-up was measured by cardiac MRI. Infarct-size measurements and BMC phenotype and function data were obtained for 101 patients (mean age, 56.5 years; mean screening ejection fraction, 37%; mean baseline cardiac MRI ejection fraction, 45%). At 6 months, 75 patients (74.3%) showed a reduction in infarct size (mean change, −21.0±17.6%). Multiple regression analysis indicated that infarct size reduction was greater in patients who had a larger percentage of CD31 + BMCs ( P =0.046) and in those with faster BMC growth rates in colony-forming unit Hill and endothelial-colony forming cell functional assays ( P =0.033 and P =0.032, respectively). Conclusions: : This study identified BMC characteristics associated with a better clinical outcome in patients with segment-elevation–myocardial infarction and highlighted the importance of endothelial precursor activity in regenerating infarcted myocardium. Furthermore, it suggests that for these patients with segment-elevation–myocardial infarction, myocardial repair was more dependent on baseline BMC characteristics than on whether the patient underwent intracoronary BMC transplantation. Clinical Trial Registration Information: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT00684021. Abstract : Supplemental Digital Content is available in the text.